Deep convolutional neural networks-based scatterer density and resolution estimators in optical coherence tomography: erratum - Thitiya Seesan; Ibrahim Abd El-Sadek; Pradipta Mukherjee; Lida Zhu; Kensuke Oikawa; Arata Miyazawa; Larina Tzu‐Wei Shen; Satoshi Matsusaka; Prathan Buranasiri; Shuichi Makita; Yoshiaki Yasuno (Biomedical Optics Express, 2024)
[This corrects the article on p. 168 in vol. 13, PMID: 35154862.].
Keywords: Optical Coherence Tomography Applications; Photoacoustic and Ultrasonic Imaging; Retinal Imaging and Analysis